2019
DOI: 10.1101/620054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Irrational risk aversion in ants is driven by perceptual mechanisms

Abstract: Animals must often decide between exploiting safe options or risky options with a chance for large gains. While traditional optimal foraging theories assume rational energy maximisation, they fail to fully describe animal behaviour. A logarithmic rather than linear perception of stimuli may shape preference, causing animals to make suboptimal choices. Budget-based rules have also been used to explain risk-preference, and the relative importance of these theories is debated. Eusocial insects represent a special… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…The evidence presented in this study adds to previous studies showing parallel value-distorting effects in humans and insects, including decoy effects (Sasaki & Pratt, 2011;Tan et al, 2014Tan et al, , 2015, risk aversion (De Agrò, Grimwade, & Czaczkes, 2019;Shafir, Wiegmann, Smith, & Real, 1999;Shapiro, 2000;Waddington, Allen, & Heinrich, 1981), discounting (Cheng, Peña, Porter, & Irwin, 2002;Wendt & Czaczkes, 2017), and expectation-driven valuation (Bitterman, 1976;Couvillon & Bitterman, 1984), suggesting that insights into human behavior can, in part, be transferred to insects. Insect-based comparative psychology studies allow much tighter control over experimental subjects and conditions, offering stringent tests of basic insights from human psychology and the experimental flexibility to test hypotheses untestable on human subjects.…”
Section: Discussionsupporting
confidence: 74%
“…The evidence presented in this study adds to previous studies showing parallel value-distorting effects in humans and insects, including decoy effects (Sasaki & Pratt, 2011;Tan et al, 2014Tan et al, , 2015, risk aversion (De Agrò, Grimwade, & Czaczkes, 2019;Shafir, Wiegmann, Smith, & Real, 1999;Shapiro, 2000;Waddington, Allen, & Heinrich, 1981), discounting (Cheng, Peña, Porter, & Irwin, 2002;Wendt & Czaczkes, 2017), and expectation-driven valuation (Bitterman, 1976;Couvillon & Bitterman, 1984), suggesting that insights into human behavior can, in part, be transferred to insects. Insect-based comparative psychology studies allow much tighter control over experimental subjects and conditions, offering stringent tests of basic insights from human psychology and the experimental flexibility to test hypotheses untestable on human subjects.…”
Section: Discussionsupporting
confidence: 74%
“…It is possible that a 0.2 M solution is near the detection limit of the ants, and as the detection limit is approached, discrimination ability also suffers, in line with basic psychophysical principles (Gescheider 1997). In a previous experiment, L. niger ants successfully learned to distinguish between 0.1 M and 0.3 M after three visits to each molarity (De Agrò et al 2019). The ants thus likely struggled to distinguish 0.2 M and 0.4 M with so few exposures.…”
Section: Discussionmentioning
confidence: 88%
“…This includes the very highly powered experiment 3 ( n = 470), which showed very good sensitivity to small changes in aversive substance, but no evidence of value distortion due to pheromone presence. In addition, a separate study (Oberhauser et al, in preparation) also showed no value distortion effects of pheromone, using identical associative learning methods to those that have been used successfully to detect many such effects in the same species ( Czaczkes et al, 2018 ; De Agrò et al, 2019 , 2020 ; Wendt et al, 2019 , 2020 ; Wendt and Czaczkes, 2020 ). Thus, while completely proving a lack of effect is not possible, we are nonetheless quite confident that pheromone trail presence does not influence perceived value in L. niger .…”
Section: Discussionmentioning
confidence: 94%